Evaluation of Some Interleukins Levels of Rheumatoid Arthritis (RA) in Baghdad province / Iraq - Rawaa Najim Alkhamessi (Zien Journals, 2023)
Autoantibodies damage and weaken joints in rheumatoid arthritis (RA), an autoimmune condition. Leukocyte (Monocyte, Lymphocyte, Mast Cell, etc.) infiltrations into the synovial compartment that cause inflammation in the synovial membrane are characteristics of RA. This study's objectives were to measure the levels of IL-6 and IL-17 in the serum in a sample of RA patients and to examine the relationship between those levels and a variety of clinical outcomes. It included fifty (50) rheumatoid arthritis patients of both sexes. They are taken from hospitals and clinics, and their ages range from (31 to) 79. The control group consists of (40) people who appear normal. The concentration of IL-6 in serum has been determined using the ELISA enzyme-linked immuno-sorbent test. The findings indicated that men have a higher prevalence of sickness than women. 30% for females against 70% for males. Regarding the age distribution of the patients, they were between the ages of 31 and 79, with a median age of 55. Compared to healthy individuals, who had an interleukin-6 concentration of 139.8– 165.88 pg/ml, the concentration in the study participants was 217.1–152.6 pg/ml. Interleukin 17 was present in patients at an average concentration of 129.19 36.88 pg/ml as opposed to 61.62 16.75 pg/ml in healthy individuals.
Keywords: Rheumatoid arthritis; IL-17; IL-6; RA